2018
DOI: 10.18052/www.scipress.com/ilns.69.12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aerosol Optical Depth Products from Multi-Satellites over Densely Populated Cities of Pakistan

Abstract: Air pollution in Pakistan is causing damage to health, environment and quality of life. Air pollution in Pakistan is not effectively monitored due to heavy cost involved in setting up ground stations. However, Satellite remote sensing can effectively monitor the air pollution in terms of Aerosol Optical Depth (AOD) at regional as well as global level. However, algorithms used to derive AOD from different sensors have some inherited differences which can pose challenges in monitoring regional AOD at high tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…(2019) estimated PM 2.5 concentration over the Indian region from the space-based AOD observations. In Pakistan, several studies have demonstrated that Moderate Resolution Imaging Spectroradiometer (MODIS) based AOD measurements are useful in understanding the seasonal and spatial variations in aerosol concentrations with a reasonable degree of accuracy ( Butt et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…(2019) estimated PM 2.5 concentration over the Indian region from the space-based AOD observations. In Pakistan, several studies have demonstrated that Moderate Resolution Imaging Spectroradiometer (MODIS) based AOD measurements are useful in understanding the seasonal and spatial variations in aerosol concentrations with a reasonable degree of accuracy ( Butt et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the aerosol concentration is due to natural aerosols including sea salt and dust particles, they may be transferred from Indian locations such as Delhi and the Thar Desert, enhanced by local sources, and then transported to the Arabian Sea. Butt et al (2018) similarly, determine that the majority of aerosols over Karachi are due to sea salt from the Arabian Sea and dust particles. Tariq and Ul-Haq (2018b) show similar outcomes of HYSPLIT backward trajectories for Karachi for the year 2013.…”
Section: Potential Trajectory and Source Contributionmentioning
confidence: 99%